How accurately do the large language models (LLMs) powering chatbots respond to questions on gender equality and women's empowerment in Indian agriculture? - Magalhaes, Marilia; Singaraju, Niyati; Koo, Jawoo (International Food Policy Research Institute, 2025)
AI-powered chatbots are emerging as a promising tool to deliver agricultural advice. Such AI-based advisory services can reach large numbers of farmers more cost-effectively than traditional extension services. They can almost instantly provide advice across more remote areas, translate technical terms into plain language, quickly adapt to local needs through feedback from users, and increase access to knowledge for marginalized groups. Yet this technology still faces many obstacles. For instance, users require access to reliable electricity and (mobile) internet, which are still unavailable in many of the world's rural farming areas.